2013
DOI: 10.1055/s-0033-1343981
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Mapping of the Temporal Branch of the Facial Nerve

Abstract: Background?Minimized frontal and frontolateral approaches have been proposed for the clipping of aneurysms and for removal of deep-seated supra- and parasellar lesions. To avoid postoperative facial nerve palsy, anatomical studies have been conducted; however, only one electrophysiological investigation has been reported. We studied the course of the facial nerve in the temporal region and identify the optimal pterional keyhole craniotomy from the perspective of facial nerve protection. Materials and Methods?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Several studies confirm that a region within 1.5 cm superio-lateral to the orbit represents a safe zone 13,24,5 . Tokimura et al 27 in his study of electrophysiological mapping of the temporal branch of the facial nerve found that akin to previous studies, the TBFN resided in a 15- to 44-mm region measuring from the orbit, the zygomatic suture, and the anterior margin of the zygomatic arch.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Several studies confirm that a region within 1.5 cm superio-lateral to the orbit represents a safe zone 13,24,5 . Tokimura et al 27 in his study of electrophysiological mapping of the temporal branch of the facial nerve found that akin to previous studies, the TBFN resided in a 15- to 44-mm region measuring from the orbit, the zygomatic suture, and the anterior margin of the zygomatic arch.…”
Section: Discussionmentioning
confidence: 80%
“…Poblete et al 5 performed 10 hemifacial cadaveric dissections and reported that the nerve to the orbicularis and frontalis muscle commonly originated from the anterior and middle trunk of the temporal nerve and crossed at a mean distance of 4 cm (range 3.5–4.5 cm, SD 3.3 mm) above the lateral canthus of the eye and the most posterior branch to the Frontalis muscle was located at a mean distance of 3.5 cm range (2.9–4.0 cm, SD 4.4 mm) posterior-superior to the lateral canthus. With reference to the lateral brow, Tokimura et al 27 recommended staying 2 cm posterosuperior to the lateral edge of the eyebrow in order to avoid injury to the TBFN. Its distance to the lateral aspect of the orbibularis oculi muscle was found to be 4.0 +/– 0.6 cm 28,29 .…”
Section: Discussionmentioning
confidence: 99%